Rhetorical Moves In Students’ Abstracts - Herlyna, Herlyna; Ramadhina, Retno; Romla, Romla (STIBA IEC JAKARTA, 2024)
Abstracts of research article are essential for increasing the visibility of the research endeavor. Creating a well-written abstract in terms of both content and rhetorical moves will ensure readers to read the entire article. Hence, the ability to write in a high level of accuracy for the production of quality abstracts is imperative. This study aims to explore the moves employed in the abstracts of Pertiwi University students majoring in Literature and English language. The data were taken from the research article abstracts of the students’ thesis. A total of thirty abstracts were randomly selected and analyzed. The study applied the five-move model for abstract analysis by Hyland (2000) to examine the occurrence and pattern of the rhetorical structures of the abstracts. A qualitative descriptive approach will be utilized in this research. The result of the study confirmed that all of the research abstracts have the first move which is the introduction, and as for the rest of the moves were applied variedly among the sample abstracts. This study suggests that, pedagogically, a more thorough effort be made to prepare the students in writing their abstracts.